(untitled) (Marketing Journal, 2025)
“Green” industrial policy is one of the directions of modern state policy, formed based on the requirements of todayʼs global climate change and sustainable economic development. It is aimed at minimizing the negative impact on the environment in industria l activities, economical use of resources and the widespread introduction of ecological innovations. This article covers the main characteristics of “green” industrial policy, namely environmental safety, reducing the carbon footprint, using renewable ener gy sources, introducing zero -waste technologies and the principles of sustainable production. The state of the local legislative framework and existing opportunities and obstacles to the development of “green” industry are identified. Based on the analysis , practical proposals are developed for improving the “green” industrial policy in Uzbekistan in legal, institutional and technological terms.